An economic evaluation of task-shifting approaches to the dispensing of anti-retroviral treatment in the Western Cape, South Africa - Foster, Nicola (Health Economics Unit, 2014)
This study aims to critically evaluate the ISPA [indirectly supervised pharmacists assistants] and nurse-based pharmaceutical care models against the standard of care that involves a pharmacist dispensing ART, on the basis of cost, and patient preference.